Postmodern Pragmatic Educology: Theoretical Issues and Models - Mažeikis, Gintautas (Acta Paedagogica Vilnensia, 2006)
The question is how do modern educational sciences guarantee successful and advanced socialization and early forms of individuation in situation of postmodern society? For this purpose the coherences between pragmatic epistemology of R. Rorty, paradigm of Service Learning and the cultural models of individuation are analysed in the article. Process of fragmentation of subject that correlates needs of modem, highly technological industry makes the most important influence on transition from normative socialization to creative individuation. The paradigms of Creative industries, Society of Dreams, theories of Conflicts, Processes, Complexity, the Action pay more and more attention to the personal individuation and try to find historical precedents or to elaborate new examples for solution of individuation strategic and tactic. Only successful individuation that corresponds or opposes socialization could guarantee necessary innovations for technological growth of modern society at the same time. Consumer exigencies for leisure time, continuous changing of stiles of life needs permanent original solutions are impossible without supporting of personal creativity. The examples of modern mythology are interpreted as a basis for development of both processes of socialization and growth of individuation. The stories about Faust, Don Quixote, Don Juan, Robinson Crusoe are examples of it. Two tendencies of individuation could be separated in the processes of development of Service learning. One of them is related to creative development of folk consciousness, for example modern mythologies, popular legends or traditions of holidays. The other tendency depends on ultimate irony, independent criticism and liberal utopia. Classical utopia for a long time was interpreted as a collective, program disposition to change social, political reality. On the contrary liberal utopia is quite personal and supports more individual, creative dreams. Pragmatism of mythopoeic is an effective in the cultural studies when mythology or rituals of communities and subcultures are developed in the process of auditorium and field studies. In the processes students help community to elaborate new vocabularies and creative approaches to the old traditions.